Is it possible to use nanocrystalline compounds in media for hypothermic storage of yeast Saccharomyces boulardii strains? - Polivanova, Olena V.; Chizhevsky, Victor V.; Vysekantsev, Igor P.; Buriak, Iryna A.; Falko, Oksana V. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 159.